Positive airway pressure for sleep-disordered breathing in acute quadriplegia: a randomised controlled trial. Issue 3 (11th December 2018) - Berlowitz, David J; Schembri, Rachel; Graco, Marnie; Ross, Jacqueline M; Ayas, Najib; Gordon, Ian; Lee, Bonne; Graham, Allison; Cross, Susan V; McClelland, Martin; Kennedy, Paul; Thumbikat, Pradeep; et al.
Abstract : Rationale: Highly prevalent and severe sleep-disordered breathing caused by acute cervical spinal cord injury (quadriplegia) is associated with neurocognitive dysfunction and sleepiness and is likely to impair rehabilitation. Objective: To determine whether 3 months of autotitrating CPAP would improve neurocognitive function, sleepiness, quality of life, anxiety and depression more than usual care in acute quadriplegia. Methods and measurements: Multinational, randomised controlled trial (11 centres) from July 2009 to October 2015. The primary outcome was neurocognitive (attention and information processing as measure with the Paced Auditory Serial Addition Task). Daytime sleepiness (Karolinska Sleepiness Scale) was a priori identified as the most important secondary outcome. Main results: 1810 incident cases were screened. 332 underwent full, portable polysomnography, 273 of whom had an apnoea hypopnoea index greater than 10. 160 tolerated at least 4 hours of CPAP during a 3-day run-in and were randomised. 149 participants (134 men, age 46±34 years, 81±57 days postinjury) completed the trial. CPAP use averaged 2.9±2.3 hours per night with 21% fully 'adherent' (at least 4 hours use on 5 days per week). Intention-to-treat analyses revealed no significant differences between groups in the Paced Auditory Serial Addition Task (mean improvement of 2.28, 95% CI −7.09 to 11.6; p=0.63). Controlling for premorbid intelligence, age and obstructive sleep apnoea severity (group effect −1.15, 95% CI −10 to 7.7) did not alter this finding. Sleepiness was significantly improved by CPAP on intention-to-treat analysis (mean difference −1.26, 95% CI −2.2 to –0.32; p=0.01). Conclusion: CPAP did not improve Paced Auditory Serial Addition Task scores but significantly reduced sleepiness after acute quadriplegia. Trial registration number: ACTRN12605000799651.